2017
DOI: 10.5812/minsurgery.44931
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Blockade, Bariatric Surgeon Satisfaction, and Quality of Patient Recovery

Abstract: Background: To date, little is known about neuromuscular blockade (NMB) and its impact in bariatric surgery and patient recovery. The goal of this study was to better assess the relationship between depth of NMB, bariatric surgeon's satisfaction, and the quality of patient recovery. Methods: Between January and September 2015, we did a prospective observational study of 50 morbidly obese patients undergoing elective laparoscopic sleeve gastrectomy (LSG) under general anesthesia at our ambulatory surgical cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…10 However, in a prospective observational study, Garneau et al found that patients in the deep group had a significantly lower duration of surgery. 19 To evaluate surgical conditions in our study, we used a 5-point SRS that has been validated in several studies. 5,6,13 Other scoring systems that have been used are the numerical rating scale (NRS) or the visual analogue scale (VAS) from 0 to 10.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, in a prospective observational study, Garneau et al found that patients in the deep group had a significantly lower duration of surgery. 19 To evaluate surgical conditions in our study, we used a 5-point SRS that has been validated in several studies. 5,6,13 Other scoring systems that have been used are the numerical rating scale (NRS) or the visual analogue scale (VAS) from 0 to 10.…”
Section: Discussionmentioning
confidence: 99%